Microglia Regulate Neuronal Circuits in Homeostatic and High-Fat Diet-Induced Inflammatory Conditions - Wang, Xiao-Lan; Li, Lianjian (Frontiers in Cellular Neuroscience, 2021)
Microglia are brain resident macrophages, which actively survey the surrounding microenvironment and promote tissue homeostasis under physiological conditions. During this process, microglia participate in synaptic remodeling, neurogenesis, elimination of unwanted neurons and cellular debris. The complex interplay between microglia and neurons drives the formation of functional neuronal connections and maintains an optimal neural network. However, activation of microglia induced chronic inflammation and increased synaptic phagocytosis lead to neuronal impairment or death. Microglial dysfunction is implicated in almost all brain diseases and leads to long-lasting functional deficiency, such as hippocampus-related cognitive decline and hypothalamus-associated energy imbalance (i.e. obesity). High-fat diet (HFD) consumption triggers hypothalamus microglial activation. Moreover, HFD-induced obesity results in cognitive deficits by triggering hippocampus microglial activation. Here, we have summarized the current knowledge of microglial characteristics and biological functions and also reviewed the molecular mechanism of microglia in shaping neural circuitries mainly related to cognition and energy balance in homeostatic and diet-induced obese conditions.